2021
DOI: 10.1002/mds.28758
|View full text |Cite
|
Sign up to set email alerts
|

Subcutaneous Levodopa Infusion for Parkinson's Disease: 1‐Year Data from the Open‐Label BeyoND Study

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 14 publications
1
12
0
Order By: Relevance
“…Evaluations of pain did not indicate any severe discomfort (pain or pruritus) associated with the nodules or any other infusion site findings. As was reported in the one year study with higher dosing regimens of ND0612, the observed nodules were generally manageable and were not a cause for discontinuation from the study [29]. However, it should be noted that this early proof of concept study employed a lower dose, and therefore smaller total volume than the dosing regiments currently being tested.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Evaluations of pain did not indicate any severe discomfort (pain or pruritus) associated with the nodules or any other infusion site findings. As was reported in the one year study with higher dosing regimens of ND0612, the observed nodules were generally manageable and were not a cause for discontinuation from the study [29]. However, it should be noted that this early proof of concept study employed a lower dose, and therefore smaller total volume than the dosing regiments currently being tested.…”
Section: Discussionsupporting
confidence: 58%
“…At the low dose used in this study, ND0612 was generally welltolerated and there were no TEAEs of dyskinesia or psychiatric symptoms reported in these patients already on long-term (mean > 7 years) levodopa therapy. In line with one year safety observations of the higher ND0612 dosing regimens currently in development [29], most patients treated with ND0612 developed transient nodules. These ISR are generally expected with SC infusion of drugs [30][31][32] and some skin reactions were also observed with placebo (saline) administration, which may be connected to the SC needle insertions.…”
Section: Discussionmentioning
confidence: 55%
“…Additionally, data from an open-label (BeyoND) study demonstrated safety with a nominally significant increase in good ON time (defined as the sum of ON-WoTD and ON time with non-troublesome dyskinesia). A treatment-emergent adverse event and common reason for discontinuation is infusion site reactions (ISRs) [ 111 , 112 ]. The long-term safety data highlighted that such ISRs are frequently mild, reversible, and could be minimized with continued training.…”
Section: Motor Fluctuationsmentioning
confidence: 99%
“…Therefore, subcutaneous administration might both avoid fluctuations in absorption resulting from delayed gastric emptying and reduce surgical risks compared to Duodopa ® ( Nilsson et al, 1998 ; Nyholm and Lennernas, 2008 ). Poewe et al (2021) evaluated the 1-year safety data of ND0612. After evaluation by 214 patients, most patients experienced infusion site reactions such as particularly nodules (30.8%) and hematomas (25.2%).…”
Section: Resultsmentioning
confidence: 99%